Tradisi dan Status Sosial dalam Penetapan Mahar Perkawinan di Gampong Mamplam Aceh Utara - M. Husen M. R.; Hamdani Hamdani; Ratri Candrasari (FISIP Universitas Malikussaleh, 2022)
This study discusses the procedure for determining the dowry in the Acehnese marriage tradition. Then the influence of social status on the value of the dowry for women in Mamplam Village, Nibong District, North Aceh Regency. We have used a qualitative approach in this study. Some data was collected by interview techniques. Analysis techniques use data reduction, data presentation, and draw conclusions or verification. The results showed that the procedure for determining the dowry in Gampong Mamplam was carried out by an application process mediated by Seulangke. Seulangke serves as a liaison between the groom and the bride. If the application from a man is accepted by the woman and her family, then after a while the process is followed up to the delivery of a dowry for the woman from the family of the man who is applying. The dowry in marriage is determined by the parents of the woman or based on the results of family deliberation. Then the value of the dowry is also strongly influenced by social status, namely the level of education and the level of wealth. If the woman comes from a rich family then the amount of dowry is quite high, it can reach the value of 20-25 mayam gold. Meanwhile, for women who come from simple families, the amount of dowry is relatively less, only around 10-15 mayam gold.